(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: The main concept of human development introduced by United Nations Development Programs (UNDP) in 1990 was to create positive growth in long term. Human development index (HDI) is formed by three dimensions, a long and healthy life, knowledge, and a decent standard of living. The purpose of this study to determine the factors affecting HDI in Indonesia in 2012-2016. We use secondary data from free publication of Central Bureau of Statistics or as known as BPS in Indonesia. The datas were from East Java in 2012-2016 with districts/ cities as unit analysis. We analyze the data with panel data regression analysis. The results is poverty significantly affect HDI in East Java, Indonesia (p<0.05). The higher HDI, the smaller percentage of poverty. Policy formulation multidimentionally is needed to reduce poverty.